Islamic Education Teacher Creativity to Improve Students' Academic Achievement at SMP Negeri 16 Gresik - Alamuddin, Imam; Muslihun, Muslihun (Anjasmoro: Islamic Interdisciplinary Journal, 2024)
Religious teacher creativity is the ability to find thoughts about new ideas in solving problems related to science, especially knowledge about Islamic religious education. Therefore, creative teachers must have an interest in finding out about the development of Islamic religious education at the moment. this and will come as an effort to increase the effectiveness of Islamic religious education. This research describes: First, to analyze the teaching creativity of teachers in learning Islamic religious education at SMP Negeri 16 Gresik. Second, to analyze the implications of the creativity of Islamic religious education teachers to improve the academic achievement of students at SMP Negeri 16 Gresik. By using qualitative research and a case study approach. Data collection techniques use interviews, observation, and documentation. The data sources are informants who are directly involved in implementing the learning activities of Pai teachers and students. The results of the research that have been examined by the author are: First, the implementation of teacher teaching creativity in Islamic religious education learning at SMP Negeri 16 Gresik. Teachers utilize three learning methods, including a) The Peer Tutor Method is a cooperative learning strategy where a sense of mutual respect and understanding is fostered between students who work together, b) The Discovery Learning Method is understanding concepts, meanings, and relationships through an intuitive process to ultimately conclude, c) Problem-Based Learning is a student-centered learning strategy, which requires students to be skilled and sensitive to solving problems in the environment. Second, the implications of the creativity of Islamic religious education teachers to improve students' academic achievement at SMP Negeri 16 Gresik: a) Discovery Learning Method, b) Problem Besed Learning, c) Problem Besed Learning, from several methods used by teacher Pai, students can understand the material well so that it influences the grades obtained, their character is formed due to learning interactions and also material regarding their attitudes, manners, and behavior.